Engineering ethics for Generation Z: a review of current approaches and proposal for future directions - Yusuff, Ikhwan; Ahmad, Zuraida; Sophian, Ali; Amir, Adibah; Hassan, Masjuki (IIUM Press, 2024)
The engineering profession has a crucial role to play in shaping the future of our society, and with the increasing complexity of technology, there is a growing need for engineers to have a strong understanding of ethical principles. This paper provides a comprehensive review of the current approaches to teaching engineering ethics, with a specific focus on how these approaches can be tailored to meet the needs of the Generation Z students. The authors examine the current approaches and its key challenges faced by this generation, such as the impact of technology on the teaching and learning approaches. The role of case studies and experiential learning in promoting ethical decision-making among this group of generation is also reviewed. Finally, the paper discusses the future directions for teaching engineering ethics, including the use of emerging technologies such as virtual and augmented reality. The paper concludes with a call for further research to better understand the ethical challenges facing the engineering profession and to develop effective strategies for addressing these challenges and for the students to internalize the importance of the ethical decision and become the agent of change in the society for the betterment of Ummah